INDUSTRI PENGOLAHAN SAPI TERPADU DI KABUPATEN GORONTALO DENGAN PENDEKATAN ARSITEKTUR HIJAU - Aswin, Hanspiter; Umar, Umar; Haisah, S (Program Studi Teknik Arsitektur, Fakultas Teknik - Universitas Ichsan Gorontalo, 2023)
This design aims to 1) figure out the macro and micro concepts in designing an Integrated Cattle Processing Industry in Gorontalo Regency, 2) find the design and application in terms of structure and arrangement using Green Architecture, and 3) realize an Integrated Cattle Processing Industry building that has adequate and proper facilities. The data collection methods used in this design are observation covering observations of internal and external conditions and through secondary data collection, namely by conducting literature studies and documents as support in design. The result of this design is located in a strategic area that follows the Spatial and Regional Plans of Gorontalo Regency, Gorontalo Province. Keyword: cattle farm, integrated cattle processing, green architectur